CONSUMERS’ BRAND LOYALTY OF ENERVON C IN PANDEMIC ERA - Hutabarat, Zoel; Putidita, Velya (Universitas Pelita Harapan, 2022)
The growth of Vitamin C demand in pandemic makes brand loyalty became one of an important factor to win competitive advantage among competitors. This study aimed to examine and understand the relationship between brand awareness, word of mouth, perceived quality, and brand image towards brand loyalty of Enervon C consumer in pandemic era. Sample of this study were 270 respondents that consume Enervon C during pandemic. This study applies quantitative research method with data collection method through electronic questionnaires. Collected data will be analyzed through SmartPLS 3.3.3 with Structural Equation Modelling. The result indicated that brand awareness, perceived quality, and brand loyalty has a direct relationship with brand loyalty and brand image mediated the relationship of brand awareness and perceived quality with brand loyalty. Word of mouth has a direct relationship with brand image.